676÷13÷[100-3÷11(79-19÷4)].
Răspunsuri la întrebare
Răspuns de
0
676 : 13: [100-3: 11 (79- 4,75)] =
=676 : 13: (100-3: 11* 74,25)=
= 676 : 13 : 100- 0,(27) * 74,25)=
= 676 : 13 :100- 0=
=52 : 100-0=
=0,52 -0 =
=0,52
=676 : 13: (100-3: 11* 74,25)=
= 676 : 13 : 100- 0,(27) * 74,25)=
= 676 : 13 :100- 0=
=52 : 100-0=
=0,52 -0 =
=0,52
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă